MICROBIAL BIOTRANSFORMATION OF (R)-(+)- LIMONENE BY Penicillium digitatum DSM 62840 FOR PRODUCING (R)-(+)-TERPINEOL BIOTRANSFORMACIÓN MICROBIANA DE (R)-(+)-LIMONENO POR Penicillium digitatum DSM 62840 PARA LA PRODUCCIÓN DE (R)-(+)-TERPINEOL - Gloria A PRIETO S (Universidad de Antioquia, 2011)
Microbial biotransformation is a relevant strategy to obtain high added value natural compounds under controlled environmentally friendly conditions. In this research work, the biotransformation of (R)-(+)- limonene using Penicillium digitatum DSM 62840 was evaluated. The study variables were the following: culture medium, pH, microorganism growth phase, substrate concentration, and inducing effect of the substrate. The results showed that a concentration of 14.7 mM limonene in the medium named malt yeast broth at a pH of 3.5, inoculated with induced spores at the early stage of the exponential growth, produces a high specificity and the highest concentration (1864 mg/L) of (R)-(+)-α-terpineol. The product obtained has a considerable potential industrial application. La biotransformación microbiana es una estrategia relevante para obtener compuestos naturales de alto valor agregado a través de procesos amigables con el medio ambiente. En este estudio se evaluó la biotransformación de (R)-(+)-limoneno utilizando Penicillium digitatum DSM 62840. Las variables estudiadas fueron: medio de biotransformación, pH, fase de crecimiento del microorganismo, concentración del sustrato y efecto inductor del sustrato. Los resultados mostraron que en medio caldo extracto de malta y levadura a pH 3,5 inoculado con esporas inducidas y crecidas en el inicio de la fase exponencial, con una concentración de limoneno de 14,7 mM, el sustrato se transformó de manera específica en (R)-(+)- α-terpineol. En estas condiciones se alcanzó la máxima concentración, 1864 mg/L. El producto obtenido tiene alto potencial de aplicación en diferentes industrias.